Periodismo deportivo y televisoras extranjeras - Briones Pérez, José Guillermo (2022)
This research project has a qualitative study because it allowed to obtain and collect information about the topic addressed, in order to analyze the editorial line of our object of study "Gol TV" in the opinion of soccer fans in Guayaquil. For the collection of descriptive and narrative data, the technique of interviewing journalists specialized in sports was used with the aim that they can give their points of view from the professional field. In addition, through observation sheets, it was possible to observe the different broadcasts of our object of study, which is the “Gol Tv” channel. Through the objectives of the research, it was possible to analyze the editorial line of Gol TV in the opinion of soccer fans in Guayaquil. Subsequently, the theoretical, legal and conceptual references on the relationship between the cable operators and the consumer were determined, to then identify the theoretical communicational bases on diffusion and public opinion and finally to analyze the interactive multimedia formats of news and sports commentary. by Goal TV.